2012
DOI: 10.1183/09031936.00116911
|View full text |Cite
|
Sign up to set email alerts
|

Cured meat consumption increases risk of readmission in COPD patients

Abstract: Recent studies have shown that a high dietary intake of cured meat increases the risk of chronic obstructive pulmonary disease (COPD) development. However, its potential effects on COPD evolution have not been tested. We aimed to assess the association between dietary intake of cured meat and risk of COPD readmission in COPD patients.274 COPD patients were recruited during their first COPD admission between 2004 and 2006, provided information on dietary intake of cured meat during the previous 2 yrs, and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
(39 reference statements)
2
25
0
2
Order By: Relevance
“…consumption of cured meats and increased risk of developing COPD [120,124,125]. A recent study has extended this association to include the evolution of the disease, revealing that high cured meat consumption is linked to a higher risk of readmission to hospital with COPD [126]. Finally, albeit rarely assessed in clinical practice, iron deficiency often occurs in COPD, which may be caused by several factors including systemic inflammation, malabsorption of iron from the gut, renal failure (as a consequence of concomitant chronic kidney disease or diabetes mellitus), and medications such as angiotensin-converting enzyme inhibitors and corticosteroids [127].…”
Section: Dietary Quality and Nutrient Deficienciesmentioning
confidence: 99%
“…consumption of cured meats and increased risk of developing COPD [120,124,125]. A recent study has extended this association to include the evolution of the disease, revealing that high cured meat consumption is linked to a higher risk of readmission to hospital with COPD [126]. Finally, albeit rarely assessed in clinical practice, iron deficiency often occurs in COPD, which may be caused by several factors including systemic inflammation, malabsorption of iron from the gut, renal failure (as a consequence of concomitant chronic kidney disease or diabetes mellitus), and medications such as angiotensin-converting enzyme inhibitors and corticosteroids [127].…”
Section: Dietary Quality and Nutrient Deficienciesmentioning
confidence: 99%
“…В 3 исследованиях сообща ется о взаимосвязи между частым или обильным потреблением копченого мяса и повышением риска развития ХОБЛ [120,124,125]. В одном из недавних исследований эта взаимосвязь распространилась на течение заболевания: показано, что обильное по требление копченого мяса больными ХОБЛ со провождается более высоким риском повторных госпитализаций [126]. Наконец, при ХОБЛ часто возникает дефицит железа, хотя это редко оценива ется в клинической практике.…”
Section: клинические рекомендацииunclassified
“…In the meantime, prior publications [11][12][13][14] and the new results of OKUBO et al [10] suggest that processed meat intake may adversely affect lung function and the risk of COPD. Although further longitudinal studies would help to clarify the nature of this association, we anticipate that well-designed, randomised trials will be needed to settle the causality of the observed epidemiological associations.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…These results are consistent with a previous cross-sectional study in a large US population showing that frequent consumption of cured meats was associated with lower forced expiratory volume in 1 s (FEV1) and FEV1/forced vital capacity and an increased risk of COPD [11], and with two longitudinal studies of male [12] and female [13] health professionals where we reported that cured meat intake was positively associated with the risk of newly diagnosed COPD. More recently, a longitudinal study of COPD patients in Spain showed that frequent consumption of cured meats was associated with more COPD exacerbations [14]. Aside from lung health, recent studies in the USA [15] and Europe [16] reported that a high consumption of processed meat was associated with higher risk of coronary heart diseases, diabetes mellitus and all-cause mortality [17].…”
Section: @Erspublicationsmentioning
confidence: 99%